Kuguacin J isolated from bitter melon leaves modulates paclitaxel sensitivity in drug-resistant human ovarian cancer cells - Pornsiri Pitchakarn (2018)
© 2017, The Japanese Society of Pharmacognosy and Springer Japan KK. We previously reported the multidrug resistance-reversing ability of kuguacin J (KJ) in cervical cancer cells via the inhibition of P-glycoprotein (P-gp) function. This study investigated whether KJ could promote cisplatin- and paclitaxel (PTX)-induced cancer cell death in drug-resistance human ovarian cancer cells (SKOV3). Cytotoxicity testing showed that SKOV3 was more resistant to cisplatin and PTX compared to drug-sensitive human ovarian cancer cells (A2780). The cytotoxicity of PTX was significantly increased in SKOV3 cells when co-treated with KJ. We found that enhancement of PTX toxicity in the cells was not related to P-gp inhibition. To elucidate the mechanism by which KJ increases PTX sensitivity, the expression of cell death involving proteins was analyzed by Western blot analysis. The results showed that PTX treatment increased the level of an anti-apoptotic protein, survivin, which may be involved in drug resistance in SKOV3. The co-treatment with PTX and KJ dramatically decreased the level of survivin and markedly induced cleavage of PARP and caspase-3, which are apoptotic-induced molecules. These findings may support the use of KJ as an effective chemosensitizer in combination with conventional chemotherapy to promote PTX sensitization in ovarian cancer patients.